THE EFFECT OF INFORMATION TECHNOLOGY AND INTERNAL CONTROL SYSTEM ON QUALITY OF FINANCIAL STATEMENTS PT BANK MUAMALAT INDONESIA TBK - nano suyatna; Nurrohman Nurrohman (Ma'soem University, 2020)
This article aims to analyze: 1) the effect of information technology on the quality of PT. Bank Muamalat Indonesia Tbk. 2) the effect of the internal control system on the quality of the financial statements of PT. Bank Muamalat Indonesia Tbk. 3) the influence of information technology and internal control systems on the quality of the financial statements of PT Bank Muamalat Indonesia Tbk. The study was conducted with a survey in the form of a questionnaire to the leaders and employees of PT. Bank Muamalat Indonesia Tbk. and self assessment through PT. Bank Muamalat Indonesia Tbk.The statistical method used is multiple linear regression analysis with data processing using the Statistical Package for Social Science (SPSS) version 22 for Windows. Previously conducted a classical test to determine the normality of data.The results of the study showed: 1) The effect of Information Technology on the quality of the financial statements of PT. Bank Muamalat Indonesia Tbk, with a value of standardized coefficient (?) of 0.096, its effect on the quality of financial statements is very low. 2) The influence of the Internal Control System on the quality of the financial statements of PT. Bank Muamalat Indonesia Tbk, with a standardized coefficient (?) of 0.669, influencing the quality of strong financial statements. 3) The effect of the simultaneous correlation coefficient on Information Technology and Internal Control Systems on the quality of the financial statements of PT. Bank Muamalat Indonesia Tbk of (R) = 73.6% is significant and the relationship that occurs is positive with a coefficient of determination (R Square) of 54.2% and the remaining 45.8% is influenced by other.Meanwhile, if seen from the calculated probability value shows that simultaneously there is the influence of Information Technology, Internal Control Systems on the quality of financial statements of PT. Bank Muamalat Indonesia Tbk.